Effect of clay and organic matter amendments on water and nutrient retention of sandy soils: column leaching experiment - Esther, Ogunniyi Jumoke; Olowookere, Bolanle T.; Burns, Ian G.; Lillywhite, Robert; Rickson, R. Jane (I I A R D Publication Company, 2021)
Two types of clay and an organic matter was used to investigate the potential of combined application of clay and organic matter (OM) to improve water and nutrient retention of sandy soils. Sandy soils are generally known to be problematic because of poor water and nutrient retention resulting in economic losses and environmental pollution. A laboratory column leaching experiment was conducted using a pure sand (PS) and a sandy loam (SL). Soils were amended with Kaolin (K) and bentonite (B) at 0, 2.5 and 5% (w/w) and peat (Pt) at 0, 10, 20, and 30% (v/v). Water and nutrient retention was simulated using ammonium nitrate at 150 kg N /ha in RO water. Water retention increased with the rate of each amendment applied, except for the SL amended with 2.5%K. Pt-clay combinations were more effective than either Pt or clay alone at the same rate. Combined application retained more water than the additive effect of Pt and clay for corresponding treatment except for 2.5%B in PS soil. For nutrient retention, all the clay amendments reduced nitrate and ammonium nitrogen losses in PS. Application of Pt, 2.5%K with or without Pt and 5%B with >20%Pt reduced nitrate leaching in SL. The results demonstrate that amending sandy soils with both clay and organic matter has potential to improve their water and nutrient retention
Keywords: nitrogen losses; water retention; kaolin; bentonite; sandy soils